SELLARS, Simon; O’HARA, Dan (Org.) Extreme metaphors: selected interviews with J.G. Ballard, 1967-2008. Londres: Fourth Estate, 2012. 510 p. - Groppo, Pedro (Aletria: Revista de Estudos de Literatura, 2013)
Resenha de Extreme metaphors: selected interviews with J.G. Ballard, 1967-2008, organizado por Simon Sellars e Dan O’Hara.